Improvement in wear resistance of C+ ion implanted DC magnetron sputtered TiC film. (December 2016) - Rani, Revati; Kumar, N.; Kumar, D. Dinesh; Panda, Kalpatru; Srivastava, S.K.; Dash, S.; Tyagi, A.K.
Abstract: DC Magnetron sputtered TiC films were subjected to C + ion implantation in order to modify the microstructure and topography. The surface roughness of implanted films increased due to ion beam induced surface bubbling and blistering. Hardness and Young's modulus values were decreased due to the amorphization of TiC crystalline phase. The adhesive strength of film-substrate interface was not influenced by C + ion implantation. The tribological results showed considerable enhancement in the wear resistance in the highest dose C + ion implanted film, compared to as-deposited TiC film. The enhanced properties are correlated to amorphization of TiC crystalline phase. Graphical abstract: Highlights: Modification of chemical and microstructural properties of C + ion implanted TiC film. Amorphization of TiC phase and microstructure softening. Significant improvement in wear resistance of C + ion implanted TiC film.